2019
DOI: 10.3233/bmr-170801
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia and aspiration pneumonia in elderly hospitalization stroke patients: Risk factors, cerebral infarction area comparison

Abstract: In stroke inpatients over sixty years of age, it is necessary to distinguish the patients with multiple previous cerebral infarctions, high NIHSS score, masticatory muscle paralysis, abolition of gag reflex for early detection and rehabilitation of dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 27 publications
1
16
0
8
Order By: Relevance
“…The well-known factors that can increase the risk of aspiration pneumonia after stroke are increased age, a higher degree of cognitive impairment, low levels of substance P or the use of angiotensin-converting enzyme inhibitors, increased severity of aspiration and dysphagia, and increased levels of post-stroke disability [5][6][7][27][28][29]. Our study's results were consistent with those of previous studies, re ected by the lower GUSS and higher PAS and NIHSS scores in the elderly group and the increased severity of the oral stage of impairment in the younger age stroke group with higher initial mRS scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-known factors that can increase the risk of aspiration pneumonia after stroke are increased age, a higher degree of cognitive impairment, low levels of substance P or the use of angiotensin-converting enzyme inhibitors, increased severity of aspiration and dysphagia, and increased levels of post-stroke disability [5][6][7][27][28][29]. Our study's results were consistent with those of previous studies, re ected by the lower GUSS and higher PAS and NIHSS scores in the elderly group and the increased severity of the oral stage of impairment in the younger age stroke group with higher initial mRS scores.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low Mini-Mental State Examination (MMSE) scores were signi cantly associated with aspiration pneumonia in supratentorial infarction, and low modi ed Barthel Index (MBI) scores and aspiration signs in video uoroscopic swallowing studies (VFSSs) and salivagrams were signi cant predictors of infratentorial infarction. Similarly, a study of elderly stroke patients showed that multiple previous episodes of infarctions, high National Institutes of Health Stroke Scale (NIHSS) scores, and masticatory muscle paralysis were associated with poststroke aspiration pneumonia [7]. However, whether individual single nucleotide polymorphisms (SNPs) can also increase this risk and make certain individuals more vulnerable than others to respiratory complications is yet to be proven.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke associated pneumonia (SAP) is one of the most fatal complications of stroke (90), and a high NIHSS score (91), dysphagia (91), and proton-pump inhibitor use (92) were found to be correlated with an increased risk of aspiration pneumonia. Disturbance of consciousness after stroke, aspiration caused by swallowing dysfunction and immunosuppression caused by stroke are considered to be the main pathogenesis of SAP (93).…”
Section: Complications and Managementmentioning
confidence: 99%
“…Stroke is one of the leading causes of disability and mortality worldwide ( 1 , 2 ). The number of stroke patients is gradually increasing around the world, leading to increases in healthcare costs ( 3 ).…”
Section: Introductionmentioning
confidence: 99%